2009 H1N1 influenza virus infection and necrotizing pneumonia treated with extracorporeal membrane oxygenation - Suntae Ji; Ok Jeong Lee; Ji-Hyuk Yang; Kangmo Ahn; Joongbum Cho; Soo In Jeong; Woo-sik Han; Yae-Jean Kim (Korean Pediatric Society, 2011)
A 3-year-old girl with acute respiratory distress syndrome due to a H1N1 2009 influenza virus infection was complicated by necrotizing pneumonia was successfully treated with extracorporeal membrane oxygenation (ECMO). This is the first reported case in which a pediatric patient was rescued with ECMO during the H1N1 influenza epidemic in Korea in 2009.